Determining Priority Service of Yogyakarta Adisutjipto Airport Using Servqual Method and Kano Model - Mikael Gabra Gani; Dewanti Dewanti; Muhammad Zudhy Irawan; Faza Fawzan Bastarianto (Journal of the Civil Engineering Forum, 2019)
Nowadays, airports are expected to be operated as a self-service organisation that provides efficient and high-quality services. Since the satisfaction of passengers is essential for airport’s operators, the efforts to provide better services for passengers become a concern for airport’s operators by increasing the quality of service to passengers. It is crucial to identify which kind of services that would be the top priority service for the passengers. Thus, this study aims to improve the quality of service to passengers that are conducted by combining the Servqual method and Kano model. Servqual method is used to capture consumer perceptions and expectations of service along with the multi-dimensional research instrument, while the Kano model is a theory to observe costumer’s satisfaction preferences. The combination of the methods aims to determine the type of service that becomes the top priority for immediate improvement so that it can improve the service quality effectively. The selection of the priority services is based on the magnitude of the gap between expectations and perceptions of passengers on a particular service, and the assessment of passengers on the type of service that significantly influences passengers’ satisfaction with the service performance at the airport. The results of this research showed that there were three types of services as the top priority for improving their performance, namely the type of services related to the personal attention to passengers, the attractive waiting room conditions, and the understanding of each passenger’s needs individually. The airport management is expected to immediately improve the performance of the services so that the quality of service can immediately increase.